Administration of vitamin D3 improves antimetastatic efficacy of cancer vaccine therapy of Lewis lung carcinoma - Zhuravel, E.; Efanova, O.; Shestakova, T.; Glushko, N.; Mezhuev, O.; Soldatkina, M.; Pogrebnoy, P.V. (Experimental Oncology, 2010)
Aim: To analyze antitumor efficacy of experimental cancer vaccine therapy combined with introduction of vitamin D3 (VD3) for treatment of Lewis lung carcinoma (3LL). Materials and Methods: Cancer vaccines composed from recombinant murine beta-defensin-2 (mBD-2) and 3LL cell lysate, or DNA, coding for mBD-2-Muc1 fusion construct cloned in pcDNA3+ vector, were prepared and used for intradermal vaccination. Experimental cancer vaccines introduced i. d. at therapeutic and prophylactic regimens to 3LLbearing C57Bl mice, were applied alone or in combination with VD3 (administered per os) and/or low-dose cyclophosphamide (CP, administered intraperitoneal). Efficacy of treatments was analyzed by primary tumor growth dynamics indexes and by metastasis rate in vaccinated animals. Results: As it has been shown, administration of the protein-based vaccine composed from mBD-2 and 3LL cell lysate in combination with VD3 and CP, but not in VD3 free setting, led to significant suppression of primary tumor growth (p < 0.005) and had significant antimetastatic effect. Introduction of VD3 with or without CP in the scheme of treatment with mBD-2-Muc1-DNA vaccine at therapeutic regimen has led to significant suppression of primary tumor (p < 0.05) and metastasis volumes (p < 0.005), while in the groups of animals treated with DNA-vaccine + VD3 with or without CP at prophylactic regimen, significant antimetastatic effect (p < 0.05) and elevation of average life-span (p < 0.05) have been registered. Conclusion: The results of this pilot study have shown promising clinical effects of VD3 administration in combination with cancer vaccinotherapy in vivo.